The Daylight And Luminous Environment Of Working Area In Library Of University Malaya - Mortazaee, Sahar (2021)
Public living conditions can be improved through several different parameters, which are effective and important. Daylighting is one of the most significant parameters. Natural light can penetrate in buildings through implementing daylighting. It also can lead to improvement of living conditions and comfort, including acoustic comfort, thermal comfort, and as well as luminous comfort. Therefore, one of the most important concern that should be considered in luminous comfort studies, is satisfaction with daylight. Although, many studies have been conducted about daylighting in buildings, in the past and recent, in a few studies, satisfaction with daylighting has been considered as a main impressive element in luminous conditions of buildings. Libraries is one of the most critical places where daylight issue should be concerned. Users’ productivity and psychological health could be boosted through the proper luminous conditions in the library. The lack of daylighting methods can be clearly observed in the University of Malaya library, where the users and staff of the library are not satisfied enough with the luminous condition. This study aimed to investigate and clearly define the factors of daylight satisfaction which have an impact on luminous comfort through some concepts that has been used in previous studies relating to this area. An attempt was then made to test the impact of these factors on luminous comfort and the effect of luminous comfort on occupants' psychological health and productivity. To achieve this objective, survey-based quantitative approach was applied. At first, a questionnaire was developed; and then, a pilot study was made to detect any deficiencies and weaknesses in the questions set